Kegiatan Kebersihan Lingkungan Secara Gotong Royong Dan Penanaman Obat-Obatan Herbal Di Taman Ibu-Ibu PKK Desa Pangombusan - Romini Junita Panggabean; Ester Viona Sihotang; Inneh Siera Nainggolan; Ledyana Dwi Mei Situngkir (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Family Empowerment and Welfare or what is commonly called PKK, is a social institution that is a working partner for the government and other social organizations in empowering and improving family welfare. This community service activity was motivated by the large number of wild grasses and community household waste that were thrown carelessly in the PKK garden in Pangombusan Village, Parmaksian District, Toba Regency. This makes the PKK park in Pangombusan village unkempt. This is due to a lack of awareness in the surrounding community, as well as the involvement of all Pangombusan village residents to participate in maintaining and preserving the PKK park, as well as a lack of awareness not to litter. In order to overcome this problem, IAKN Tarutung KKN students took part in activities to clean the Pangombusan village environment and re-green the PKK park by planting several types of herbal medicines, such as: ginger, turmeric, lemongrass, galangal, galangal and jerango.